2000
DOI: 10.1590/s0102-311x2000000400017
|View full text |Cite
|
Sign up to set email alerts
|

Os Consórcios Intermunicipais de Saúde e o Sistema Único de Saúde

Abstract: Municipalities (or counties)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
52

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 1 publication
(1 reference statement)
0
10
0
52
Order By: Relevance
“…Since most of these small and/or remote communities have small populations, they suffer from inadequate human and financial resources and infrastructure 28 . Mendes et al 29 presented the results of a study in a state capital in Northeast Brazil which revealed great dissatisfac-Cad.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of these small and/or remote communities have small populations, they suffer from inadequate human and financial resources and infrastructure 28 . Mendes et al 29 presented the results of a study in a state capital in Northeast Brazil which revealed great dissatisfac-Cad.…”
Section: Discussionmentioning
confidence: 99%
“…Primeiro, devido ao pequeno porte de grande parte dos municípios que enfrentaram dificuldades no planejamento e na organização dos seus sistemas 8 ; depois, pela distribuição desigual da oferta de recursos humanos e da capacidade instalada 9 e, por fim, pelas características dos governos municipais e da gestão dos sistemas locais 10 .…”
Section: Introductionunclassified
“…Entretanto, se claro está que os consórcios resultam em vantagens para os municí-pios consorciados e sua população, como apontam alguns estudos, as razões da sua indução e da sua sustentabilidade necessitam de maior investigação e são objeto comum de controvér-sia 14,15,16,17,18,19,20,21,22,23,24,25,26 .…”
Section: Introductionunclassified